MOLDOVAN AGRI-FOOD EXPORT POTENTIAL ASSESSMENT IN THE CONTEXT OF COMPETITIVE PERFORMANCE - Aurelia LITVIN; Cornel COSER; Eugeniu LITVIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to present the assessment of the agrifood export potential of the Republic of Moldova. The data involved came from Moldavian balance sheet, as well as international trade data like Comtrade, UNCTAD Statistics. During the analyzed period the national agrifood export potential suffered crucial downturns in terms of performance and volume (value) diminutions. The most affected were the High Value Added products, such as fruit, milk, meat. This transposed in major revenue losses from performing export.Internally, reserves confirming Moldova's agrifood export potential are still untapped and export performance still low compared to Moldova’s competitors in the regional agrifood markets.